Effects of Esterified Hyaluronic Acid, Adipose Tissue, and Blood Glue on Survival of Diced Cartilage Grafts - (:unkn) unknown (My University, 2021)
OBJECTIVES: Diced cartilage grafts are used for correcting nasal dorsal deformities and irregularities. However, cartilage resorption is among most common problems after rhinoplasty. The purpose of this experimental study was to investigate the effects of esterified hyaluronic acid, adipose tissue, and blood glue on the viability of diced cartilage grafts. METHODS: A total of 24 Wistar albino rats were used for the study. Cartilage grafts were obtained from 1 side ear and diced. The rats were divided into 4 groups (6 in each group): bare diced cartilage (group 1), diced cartilage wrapped with adipose tissue (group 2), diced cartilage blended with blood glue (group 3), and diced cartilage wrapped with esterified hyaluronic acid (group 4). The grafts were inserted into the subcutaneous pockets of the back of same rat. After 2 months follow-up specimens were harvested for histopathological and dimensional examination. The sections were stained with Hematoxylin and Eosin, Masson-Trichrome, and Elastic Van-Gieson. Chronic inflammation, loss of chondrocyte nucleus, vascularization, foreign body reaction, collagen content of matrix, and extent of elastic fiber were assessed under light microscopy. RESULTS: Foreign body reaction in adipose tissue and blood group was significantly higher than bare cartilage and esterified hyaluronic acid group (P = 0.001). With respect to loss of chondrocyte nucleus esterified hyaluronic acid group had significant higher rate of nucleus loss than other groups (P = 0.002). CONCLUSIONS: This study suggests that blood glue, esterified hyaluronic acid and autologous adipose tissue have not beneficial effects in improving viability of diced cartilage grafts.